2009
DOI: 10.2178/jsl/1231082314
|View full text |Cite
|
Sign up to set email alerts
|

Stacking mice

Abstract: We show that either of the following hypotheses imply that there is an inner model with a proper class of strong cardinals and a proper class of Woodin cardinals. 1) There is a countably closed cardinal κ ≥ ℵ such that □κ and □(κ) fail. 2) There is a cardinal κ such that κ is weakly compact in the generic extension by Col(κ, κ+). Of special interest is 1) with κ = ℵ3 since it follows from PFA by theorems of Todorcevic and Velickovic. Our main new technical result, which is due to the first author, is a weak co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 12 publications
2
81
0
Order By: Relevance
“…If a maximal K c construction converges to a transitive inner model containing the ordinals then the resulting model has covering properties. For instance, the authors of [2] introduced a K c construction and showed that if it converges to a transitive inner model containing the ordinals and κ is an inaccessible cardinal then, assuming there is no inner model with a superstrong cardinal, cf(Ord ∩ S(K c |κ)) ≥ κ where S is the stack of all countably iterable mice extending K c |κ and projecting to κ.…”
Section: V [G] "P[t ] = (P[s]) C " a Set Of Reals A Is Called Univmentioning
confidence: 99%
“…If a maximal K c construction converges to a transitive inner model containing the ordinals then the resulting model has covering properties. For instance, the authors of [2] introduced a K c construction and showed that if it converges to a transitive inner model containing the ordinals and κ is an inaccessible cardinal then, assuming there is no inner model with a superstrong cardinal, cf(Ord ∩ S(K c |κ)) ≥ κ where S is the stack of all countably iterable mice extending K c |κ and projecting to κ.…”
Section: V [G] "P[t ] = (P[s]) C " a Set Of Reals A Is Called Univmentioning
confidence: 99%
“…Baumgartner showed that the proper forcing axiom PFA (see subsection 1.2) is consistent relative to the existence of supercompact cardinals, see Shelah [18,Chapter VII]; it is widely expected that, once fine structural inner model theory has been developed enough, it will be shown that PFA is in fact equiconsistent with a strong large cardinal axiom. The best available result to date is from Jensen-SchimmerlingSchindler-Steel [9], where it is shown that PFA implies the existence of nondomestic mice (see subsection 1.3), see also Andretta-Neeman-Steel [1].…”
Section: Large Cardinal Axioms See Kanamorimentioning
confidence: 99%
“…Many consequences of PFA can be considered natural features of the universe of sets (for example, the failure of the continuum hypothesis, the failure of square principles, the singular cardinal hypothesis, determinacy in L(R), and generic absoluteness of L(R); see for example Bekkali [3], Todorčević [20], Viale [22], and Jensen-Schimmerling-Schindler-Steel [9]) thus providing evidence for its acceptance as a natural extension of ZFC. However, even if one does not consider PFA to be "natural", it seems reasonable that some common features of forcing axioms and other similar strong reflection principles will eventually be considered as natural as large cardinal axioms.…”
Section: Forcing Axiomsmentioning
confidence: 99%
“…13 See [Fuc08] and [JSSS07] for a further discussion. The strength of a non-domestic mouse exceeds what is known as the AD R hypothesis.…”
Section: Definition 213 ([Men74]mentioning
confidence: 99%